Efeitos inibitórios da sertralina no sistema urinário de ratos - Magalhães, Patrícia Andrea da Fonseca (2010)
Sertraline, a drug belonging to the family of selective serotonin reuptake inhibitors, is used in antidepressant therapy, and has good tolerance with low incidence of side effects. Here we have characterized the pharmacological effects of sertraline on the pattern of voiding anesthetized rats, on the renal functional parameters of isolated rat kidney and on the contractile parameters of isolated bladder and mesenteric smooth muscle. In vitro, strips of urinary bladder and rings of mesenteric artery were kept in physiological solution aerated with 95% O2 - 5% CO2, pH 7.4, 37°C, for the record of isometric muscle contractions. We also used isolated rat kidney perfused with modified Krebs-Henseleit solution containing 6% bovine albumin (37°C, 95% O2 - 5% CO2). In vivo, urinary bladder of anesthetized rats was continuously infused with saline at room temperature (23°C) via an infusion pump set to flow 0.06 mL/min and urinary parameters were evaluated after administration of sertraline. In these experiments, sertraline (20 mg/kg, i.v.) significantly increased voiding frequency (control = 0.16 ± 0.02 urination/min to 0.70 ± 0.09 urination/min), basal pressure of filling (control = 4.18 ± 2.11 cmH2O to 25.38 ± 3.03 cmH2O) and maximum bladder pressure reached during the bladder contractions (control = 25.78 ± 2.11 cmH2O to 40.88 ± 3.03 cmH2O). In isolated kidneys, previous administration of sertraline (30 µM) inhibited the changes promoted by phenylephrine (10-4 M) in perfusion pressure (PP; 178.31 ± 21.68 mmHg to 105.40 ± 14.46 mmHg), renal vascular resistance (RVR, 6.82 ± 0.99 mmHg/mL.g-1.min-1 to 4.32 ± 0.55 mmHg/mL.g-1.min-1), urinary flow (UF; 0.43 ± 0.15 mL.g-1.min-1 to 0.08 ± 0.03 mL.g-1.min-1) and the rate of glomerular filtration rate (GFR, 1.60 ± 0.40 mL.g-1.min-1 to 0.32 ± 0.17 mL.g-1.min-1). In isolated strips of rat urinary bladder, sertraline inhibited, in a concentration-dependent manner, the contractions induced by 60 mM K+ or 3 µM carbachol (CCh) with IC50 of 21.0 [15.8 to 28.0] µM and 22.8 [12.9 to 40.4] µM, respectively. Added to the plateau of a steady state contraction induced by K+ (60 mM) or CCh (1 µM), sertraline produced relaxing effect, in a concentration-dependent manner, with IC50 of 94.3 [42.2 to 146.4] µM and 67.8 [20.1 to 115.5] µM, respectively. In rings of mesenteric artery stimulated by K+ (60 mM) or PHE (60 µM) in medium without Ca2+ with EGTA (0.5 mM), sertraline (100 µM) inhibited contractions induced by Ca2+ from 124.1 ± 8.1% to 48.3 ± 14.0% and 74.8 ± 13.5% to 35.9 ± 9.4% respectively. In conclusion, sertraline increased the urinary frequency voiding in anesthetized rats, inhibited the changes induced by PHE in isolated kidney and its effects probably are caused by its vascular antispasmodic actions. This hypothesis was confirmed by the inhibitory effects on bladder smooth muscle strips and mesenteric artery rings, which are promoted by a possible interference of sertraline with the Ca2+ influx through plasmalemmal channels, which may be receptor- or voltage-operated Ca2+ channels.